A Questão Ambiental. Desafios Políticos, Econômicos e Ideológicos Na Perspectiva Brasileira - Luiz Alberto Leandro (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2016)
From the perspective of the Brazilian government, the economies of emerging markets must take economic leadership on a global scale. This growth indicated by the government has highlighted more the serious social environmental conflicts. The consolidation of a market for mass consumption along the lines of the Northern nations seems to be incompatible with a sustainable environmental policy. This essay aims to contribute to the understanding of the contradictions present in embedded development proposals within the contemporary capitalism and reflect on the contradictory nature of the system that gives rise to different ideas and goals for environmental issues in the Brazilian context. This article was based on an exploratory research method and organized using a bibliographic research. We use the evaluation categories to guide the analysis. We believe that from a systemic effort, where government and society recognize that the development concept differs from the concept of economic growth, it will be possible to build a more balanced way.